The Oxford first companion to music - McLeish, Kenneth 1940- (Oxford University Press, 1982)
Chapter titles include "Music round the World," "Instruments and Orchestras," "Singing and Dancing," "The Story of Music," "Composers and Their Music," and "Writing Music."